Adventures in missing the point - McLaren, Brian D. (Zondervan, 2003)
Salvation -- Theology -- Kingdom of God -- End times -- The Bible -- Evangelism -- Social action -- Culture -- Women in ministry -- Leadership -- Seminary -- Environmentalism -- Homosexuality -- Sin -- Worship -- Doubt -- Truth -- Being postmodern.